2021
DOI: 10.1680/jgrim.18.00053
|View full text |Cite
|
Sign up to set email alerts
|

Engineering properties of clayey soil stabilised with alkali-activated slag

Abstract: The effects of alkali-activated slag on the engineering properties of clayey soil were investigated. The mix proportion parameters were chosen by using Taguchi's experimental design methodology. Four factors (groundgranulated blast-furnace slag content, concentration of sodium hydroxide solution, sodium hydroxide-to-sodium silicate weight ratio and alkaline solution-to-slag weight ratio) were assessed in order to obtain the greatest compaction properties, uniaxial compressive strength and California bearing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The geopolymer based on blast-furnace slag is a binder which could have a high strength at room temperature. Davari et al [17] investigated the influence of alkali activated slag on the main properties of clayey soil. It was concluded that the most significant factor was the weight ratio of alkaline solution and slag.…”
Section: Introductionmentioning
confidence: 99%
“…The geopolymer based on blast-furnace slag is a binder which could have a high strength at room temperature. Davari et al [17] investigated the influence of alkali activated slag on the main properties of clayey soil. It was concluded that the most significant factor was the weight ratio of alkaline solution and slag.…”
Section: Introductionmentioning
confidence: 99%